Advancing emergency department–initiated buprenorphine. Issue 3 (16th June 2021) - Huntley, Kristen; Einstein, Emily; Postma, Terri; Thomas, Anita; Ling, Shari; Compton, Wilson
Abstract: Opioids are the main driver of drug overdose deaths in the United States, and there has been a marked increase in opioid‐related overdoses during the COVID‐19 public health emergency. Many emergency departments (EDs) across the country are implementing ED‐initiated buprenorphine programs, and this is a method to address and prevent opioid overdoses. Resources are available to overcome barriers and take action.